2014
DOI: 10.4304/jsw.9.1.76-81
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Model of Requirements Change Impact Analysis

Abstract: Software systems are critical assets to organisations as they support important business processes and workflow. To maintain the value of these assets, the requirements of software systems must evolve whenever there are changes in business needs. A key problem to organisations is implementing requirements change to the existing software systems. Such initiatives need proper analyses so that their effects could be determined before resources are spent. Impact analysis is therefore an important step in requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…The qualitative part consists of literature review and focus group study which have been conducted earlier to gather the identified risk factors as well as to confirm them. The findings have been reported in [19]. However, the findings from empirical study was only validated solely through opinion-based perspective, thus it should be refined and strengthen further by confirming the risk factors quantitatively through a large scale survey.…”
Section: Methodsmentioning
confidence: 84%
See 3 more Smart Citations
“…The qualitative part consists of literature review and focus group study which have been conducted earlier to gather the identified risk factors as well as to confirm them. The findings have been reported in [19]. However, the findings from empirical study was only validated solely through opinion-based perspective, thus it should be refined and strengthen further by confirming the risk factors quantitatively through a large scale survey.…”
Section: Methodsmentioning
confidence: 84%
“…Fig. 2 below illustrates a conceptual model of requirements change implementation which was based on previous conceptual model work [19]. The conceptual model was updated with the empirical output from the focus group to produce the model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Penilaian peringkat resiko khususnya melibatkan identifikasi resiko, analisis resiko dan penentuan prioritas resiko [19]. Hal ini sangat penting karena dapat menentukan penilaian resiko terhadap perubahan-perubahan yang akan terjadi [20]. Dampak resiko ini dilihat dari data RPO, RTO dan MTD yang telah dikumpulkan.…”
Section: Metode Penelitianunclassified